Meta‐analysis: the risk of venous thromboembolism in patients with inflammatory bowel disease. Issue 10 (2nd April 2013) - Yuhara, H.; Steinmaus, C.; Corley, D.; Koike, J.; Igarashi, M.; Suzuki, T.; Mine, T.
Summary: Background: Inflammatory bowel disease (IBD), which includes Crohn's disease (CD) and ulcerative colitis (UC), is a systemic disorder that predominantly affects the bowels but is also associated with venous thromboembolism (VTE). Aim: To provide a quantitative assessment of the association of IBD with venous thromboembolism risk and to explore the possible sources of heterogeneity in the current literature, a meta‐analysis of case–control and cohort studies was conducted. Methods: Studies were identified by a literature search of the PubMed and Scopus databases (from inception inclusive 31 December 2012) for English language studies. Summary relative risks (RRs) with 95% confidence intervals (CIs) were calculated with fixed‐ and random‐effects models. Several subgroup analyses were performed to explore potential study heterogeneity and bias. Results: Eleven studies met our inclusion criteria. The summary RR for deep venous thromboembolism (DVT) and pulmonary embolism (PE) comparing subjects both with and without IBD was 2.20 (95% CI 1.83–2.65). After adjusting for obesity and smoking, summary relative risks near 2.0 were seen for venous thromboembolism in both UC and CD patients. Conclusion: This meta‐analysis showed that inflammatory bowel disease is associated with an approximately two‐fold increase in the risk of venous thromboembolism.